An in vivo platform to select and evolve aggregation-resistant proteins - Jessica S. Ebo (Nature Portfolio, 2020)
Protein aggregation remains a significant challenge for manufacturing of protein biopharmaceuticals. Here, the authors demonstrate the use of directed evolution and an assay for in vivo innate protein aggregation-propensity to generate aggregation-resistant scFv fragments.